On the solvability of one class of parameterized operator inclusions - Kapustyan, V. O.; Kasyanov, P. O.; Kohut, O. P.; Капустян, В. О; Касьянов, П. О.; Когут, О. П. (Institute of Mathematics, NAS of Ukraine, 2008)
We consider a class of parameterized operator inclusions with set-valued mappings of \( {\bar S_k} \) type. Sufficient conditions for the solvability of these inclusions are obtained and the dependence of the sets of their solutions on functional parameters is investigated. Examples that illustrate the results obtained are given.